Infrastruktur Jalan Terhadap Peningkatan Kinerja Ukm Tas - Muniroh, Leny (inovator, 2018)
The research objective are to analyze handbag Small-Medium Enterprise (SME) performance and the effect of infrastructure development on MSE performances in Bojong Rangkas Village, District of Ciampea, Bogor Regency. The research conducted from Pebruary to May 2010. Primary and secondary data use to the purposes. The sampling consisted of 30 SME respondents for observation period 2008 and 2009. The production function specified using Cobb-Douglass. The regression results indicated the model significant at ? = 0.05. Sig-t test indicates that all independent variables shows positive sign. At ? = 0.30, labor (0.172), material (0.000) and dummy year (0.272) has positive and significant effect on production. This result indicate that road infrastructre development has positive effect on handbag SME production. As reccomendation, there is a need another support such as soft infrastructure (training) to realize the location as center of handbag SME in the regency